Parametric analysis of the impact of windows on energy needs of buildings with energy passive house standard - Cvetkovska, Meri; Trpevski, Strahinja; Andreev, Andrej; Trombeva Gavriloska, Ana; Lazarevska Marijana (My University, 2015)
The goal of this paper is to present the window parameters that mostly affect the design of passive houses, as well as of all kinds of energy efficient buildings. the solar factor, or permeability of the light glazing, is of a crucial importance for the total energy needs. At the same time there is a risk of overheating during the hot summer. Because of these features, the windows are key elements in achieving the passive house standard. The analysis of the variations of the three basic parameters, as: influence of the size of the windows in facade elements, the type of glass in windows and the type of window frames give a clear picture of the impact of each of these parameters as well as of their combination on the energy needs of the Passive House that is treated in this paper. This paper refers to the analysis of buildings in the Macedonian climate conditions.
Keywords: passive house, energy demand, solar factor, energy transmittance, overheating